Enhancing Career Development for Engineering Students Through Role Play: Developing English Speaking Skills For Professional Settings - Sakinah, Yanik Lailinas; Sari, Candrika Citra; Imron, Aly (Journal of Language and Literature Studies, 2025)
This study explores the implementation of role-play activities in enhancing English speaking skills for engineering students, particularly in the context of career development. The research was conducted with 20 fifth-semester students enrolled in the Electrical Power System Engineering program at the State Polytechnic of Malang, who were enrolled in the English for Career Development (ECD) course. A descriptive qualitative design was employed, utilizing observation and questionnaires to assess the effectiveness of role-play in improving students' speaking abilities, focusing on areas such as vocabulary acquisition, confidence, and professional communication. The role-play activity centered around job interviews, where students took on the roles of both interviewer and interviewee, requiring them to engage with professional language and real-world scenarios. The results indicated that role-play significantly enhanced student participation, with the highest scores observed in the participation aspect. The students also showed notable improvements in vocabulary use, confirming the role-play's ability to activate and expand students' vocabulary in a professional context. However, the study also revealed challenges in grammar, particularly in tense usage, which impacted clarity and accuracy. The feedback provided to students helped address these issues. Additionally, the questionnaire results highlighted the positive impact of role-play on students' motivation, knowledge, skills, and attitudes, indicating that the technique fosters active engagement and enhances soft skills. The findings suggest that role-play is a valuable tool for improving English speaking skills among non-English major students, especially in technical fields, and can be effectively integrated into language curricula for career development.